2005
DOI: 10.1111/j.1742-7843.2005.pto_973112.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Superoxide Anion Generators on Responses to Exogenous Nitric Oxide and Non‐Adrenergic, Non‐Cholinergic Nerve Stimulation in Rat Isolated Penile Bulb

Abstract: The effects of the superoxide anion generators, pyrogallol and hydroquinone on relaxations induced by electrical field stimulation (70 V, 0.7 msec., 0.5-8 Hz for 5 sec.) and exogenous nitric oxide donor sodium nitroprusside, were investigated in rat penile bulb precontracted with phenylephrine (10 ª4 M). Pyrogallol (10 ª4 M, 3¿10 ª4 M) and hydroquinone (3¿10 ª4 M) reduced the relaxations induced by sodium nitroprusside, but had no effect on relaxations elicited by nitrergic nerve stimulation. After treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Nitric oxide has been found to be co‐localized with Cu/Zn superoxide dismutase in neuroeffector junctions and is protected from destruction by superoxide anions via this enzyme in mouse anococcygeus [15], bovine retractor penis [16] and rat anococcygeus [17] muscles. Our recent finding that relaxations to electrical field stimulation were reduced by superoxide anion generators after inhibition of endogenous Cu/Zn superoxide dismutase with DETCA presents strong evidence about the existence of the above mentioned protection in rat penile bulb [9]. However, in the present study, the relaxant responses to electrical field stimulation were found unchanged after 2 or 24 hr of detorsion following torsion.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Nitric oxide has been found to be co‐localized with Cu/Zn superoxide dismutase in neuroeffector junctions and is protected from destruction by superoxide anions via this enzyme in mouse anococcygeus [15], bovine retractor penis [16] and rat anococcygeus [17] muscles. Our recent finding that relaxations to electrical field stimulation were reduced by superoxide anion generators after inhibition of endogenous Cu/Zn superoxide dismutase with DETCA presents strong evidence about the existence of the above mentioned protection in rat penile bulb [9]. However, in the present study, the relaxant responses to electrical field stimulation were found unchanged after 2 or 24 hr of detorsion following torsion.…”
Section: Discussioncontrasting
confidence: 67%
“…Ischaemia reperfusion injury has been associated with the overgeneration of reactive oxygen and nitrogen species [8]. In our previous study, we found that oxygen‐free radicals reduced nitrergic nerve‐mediated relaxant responses only in the presence of an inhibitor of endogenous Cu/Zn superoxide dismutase in rat penile bulb [9]. Besides, we have recently demonstrated that unilateral testicular torsion in the rat reduces neurotransmitter release from nerve terminals in the ipsilateral vas deferens [7].…”
mentioning
confidence: 99%